Total Antioxidant Capacity and Total Oxidant Status in Perinatal Asphyxia in Relation to Neurological Outcome - Aydemir, O.; Akar, M.; Uras, N.; Eras, Z.; Erdeve, O.; Oguz, S. S.; Dilmen, U. (Neuropediatrics, 2011)
This study aimed to investigate the global oxidant/antioxidant status of infants with perinatal asphyxia and its relation to neurological outcomes. A prospective controlled study including term infants with perinatal asphyxia was conducted. Blood samples were obtained from patients and controls at 6–24 h and on the 3rd day of life for TAC and TOS measurement and OSI values were calculated. Neurodevelopment was evaluated at 12 months of age in survivors using Bayley scales of infant development II (BSID II). 17 term infants with perinatal asphyxia and 17 healthy controls were enrolled. On the first day of life TAC, TOS and OSI were significantly higher in patients with perinatal asphyxia (p<0.001). Total antioxidant capacity decreased significantly on day 3 compared to first day of life in the patient group (p=0.04). Infants with seizures and abnormal amplitude-integrated electroencephalography recordings had higher TOS and OSI levels in the 1st day. There was no correlation between TAC, TOS and OSI levels and BSID II scores. In conclusion oxidant/antioxidant balance is disturbed in favour of oxidants in perinatal asphyxia. Degree of oxidative stress is related to severity of neurological involvement in the first days of life.
Keywords: hypoxic-ischemic encephalopathy; newborn; neurological outcome; oxidative stress; seizures